Advances in Immuno-oncology for the Treatment of Colorectal and Anal Cancers - Uboha, Nataliya V.; Grogan, Patrick T.; Deming, Dustin A. (Digestive Disease Interventions, 2021)
Immune checkpoint inhibitors changed treatment paradigms across several malignancies. With the exception of tumors with microsatellite instability (MSI-H), gastrointestinal cancers have been largely resistant to these agents. Herein, we review the data supporting the use of immunotherapy for patients with (MSI-H) colorectal tumors. We discuss ongoing research and answered questions regarding resistance and sequence of use of these agents for this disease. We discuss ongoing research efforts to augment activity of these agents in microsatellite stable colorectal cancer. We also provide an overview of the data and ongoing studies immune checkpoint inhibitors in the treatment of anal cancer.
Keywords: colorectal cancer; anal cancer; immune-oncology; immune checkpoint inhibitors; microsatellite instability; mismatch repair deficiency; clinical trials